Antecedents and outcomes of green brand image: Perspectives from guests of DOT-accredited hotels - Victoria Madeleine B. Reveche; Junalyn M. Tague; Vicente S. Maravilla (Journal of Economic, Business & Accounting Research, 2026)
Background: Amid growing calls for environmental accountability in hospitality, this study explores how Green Brand Image mediates the relationship between perceived Green Brand Benefits both functional (e.g., eco-friendly operations) and emotional (e.g., environmental self-expression) and brand outcomes such as trust, loyalty, preference, and perceived sustainable corporate image. Drawing from associative network theory and the hierarchy of effects model, the study builds on recent literature emphasizing the cognitive and affective processes driving green consumer behavior. Methods: Data were collected from 260 guests who stayed at Department of Tourism (DOT)-accredited accommodations in Cebu City, Philippines. Using a structured survey and analyzed through Structural Equation Modeling (SEM). Findings: Study reveal that emotional benefits (β = 0.607, p <0.001) have a more substantial impact on Green Brand Image than functional benefits (β = 0.284, p <0.001). Green Brand Image significantly influences trust (β = 0.740), loyalty (β = 0.716), preference (β = 0.679), and sustainable corporate image (β = 0.743), all at p <0.001. Full mediation was confirmed across all pathways (H8a–H8h), suggesting that brand outcomes are realized only when green benefits are internalized through a credible and emotionally engaging brand image. These results validate the role of emotional engagement in sustainability marketing and highlight the image construct as a decisive conduit for influencing consumer behavior. Conclusion: The study concludes that hotels must combine authentic environmental initiatives with emotionally resonant storytelling to build consumer trust and long-term brand equity. Novelty/Originality of this article: The novelty of this study lies in empirically demonstrating the full mediating role of Green Brand Image in an emerging Southeast Asian tourism context, where green branding is still evolving.